Ethnomedicinal, Phytochemicals, and Pharmacological Aspects of Sentul (Sandoricum koetjape) - Made Dharmesti Wijaya (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2022)
Sentul (Sandoricum koetjape) is a tropical plant that has been used as traditional medicine in some Asian countries for decades. Research on phytochemicals and pharmacological activities of this plant extracts has been conducted and shows promising medicinal properties. This review aims to integrate knowledge about S. koetjape focusing on three main aspects namely ethnomedicinal, phytochemicals, and pharmacological, in order to encourage further research on this plant for future drug development. Traditionally, all plant parts of S. koetjape have been used for treating various health problems and diseases such as diarrhea, fever, colic, and leucorrhoea. More than 30 chemicals have been identified from S. koetjape, which the most important compounds are ring-A secotriterpene, oleane-type triterpene, secomultiflorane-type triterpene, hydroxymultiflorane triterpene, and limonoids. In vitro studies showed pharmacological potential of the extracts and phytochemicals constituents of S. koetjape including antibacterial, antifungal, antitumoral, anticancer, insecticide, and antioxidant.